An exploratory study evaluated the 30 most commonly reported medications in the United States food and drug administration’s adverse event reporting system that are associated with the occurrence of kidney stones - Bao, Erhao; Yang, Yang; Jiang, Binglei; Wang, Ben; Liu, Ying; Yang, Lin; Xia, Long; Zhu, Pingyu (Frontiers in Pharmacology, 2024)
Objective This research project aimed to identify and analyze the top 30 drugs most commonly associated with kidney stone formation using data from the U.S. Food and Drug Administration’s Adverse Event Reporting System (FAERS) database. The study will focus on determining the reported Odds ratio (ROR) and Proportional Report ratio (PRR) of each identified drug to assess its potential risk of contributing to the development of kidney stones in order to effectively manage and reduce the overall burden of kidney stones worldwide. Background Kidney stones are a common urinary system disease, and their formation is influenced by multiple factors, including medications, metabolic syndrome, environmental factors, genetic susceptibility, urinary tract abnormalities, and obstructive pathology. Among these factors, medications are an important and clearly defined cause of kidney stone formation. Currently, drug-induced kidney stones account for 1%–2% of all cases of kidney stones. Although the proportion may appears modest, its contribution to the overall prevalence of kidney stones should not be overlooked. The high incidence and frequent recurrence of kidney stones pose significant challenges to prevention efforts. Therefore, a thorough understanding of which medications may trigger stone formation is crucial for effectively managing and reducing the burden of this global health issue. Method This study utilized the FDA Adverse Event Reporting System (FAERS) database maintained by the U.S. Food and Drug Administration to extract raw data from 1 January 2010, to 31 March 2024. Duplicate data was removed following the FDA-recommended method. Subsequently, data related to drug-induced kidney stones was extracted by linking the DEMO table, DRUG table, and REAC table using specific primaryid numbers, resulting in a total of 37,781 drug records and 37,027 demographic records. The data was sorted based on the frequency of drug-induced kidney stones, and the top 30 drugs associated with kidney stone formation were selected for analysis. The primary analytical methods employed were disproportionality analyses, calculating the Reporting Odds Ratio (ROR) with its 95% Confidence Interval (CI) and Proportional Reporting Ratio (PRR) to reveal the association between drugs and adverse kidney stone events. Results We ranked the 30 most common drugs based on their ROR and PRR values. The three drugs most commonly associated with kidney stones were Atazanavir (ROR 46.35, 95% CI 43–50, PRR 44.9), Topamax (ROR 19.44, 95% CI 17.66–21.40, PRR 19.19), and Prevacid (ROR 12.67, 95% CI 11.62–13.82, PRR 12.57). Drug categories most commonly associated with kidney stones were antiretroviral drugs, proton pump inhibitors, and antiepileptic drugs. Conclusion Our research has summarized a list of potential drug categories associated with kidney stones. Clear understanding of the risk and frequency of drug-induced kidney stones caused by specific medications can reduce the likelihood of patients developing the condition. Clinical doctors should keep vigilant during diagnosis and treatment processes, and communicate relevant risk information to patients.